SETD8 potentiates constitutive ERK1/2 activation via epigenetically silencing DUSP10 expression in pancreatic cancer. (28th February 2021) - Liu, Mengqi; Qin, Yi; Hu, Qiangsheng; Liu, Wensheng; Ji, Shunrong; Xu, Wenyan; Fan, Guixiong; Ye, Zeng; Zhang, Zheng; Xu, Xiaowu; Yu, Xianjun; Zhuo, Qifeng
Abstract: Constitutive ERK1/2 activation has been frequently observed in pancreatic adenocarcinoma (PDAC). How ERK1/2 activation status been potentiated and maintained by epigenetic mechanisms has seldom been discussed in PDAC. In this study, we first examined the expression status of p -ERK1/2 in PDAC tissues by immunohistochemical staining and then screened possible epigenetic factors that displayed different expression status between p -ERK1/2 high and low groups by RNA profiling, and found that SETD8 displayed an increased expressional pattern in p -ERK1/2 high patient group. Then the impact of SETD8 on the proliferation of PDAC cells were investigated on the basis of gain or loss-of-function assays. RNA sequencing assays were performed to screen potential SETD8 downstream targets that contribute to ERK1/2 activation. Mass spectrometry and transcriptional analysis, including dual-luciferase assay and chromatin immunoprecipitation assay (ChIP), were used to explore the molecular mechanisms that governing SETD8-mediated ERK1/2 activation. In vitro cell line studies and in vivo xenograft mouse model studies indicated that SETD8 promoted cell proliferation and increased tumor formation capacity of PDAC cell lines. Mechanism explorations uncovered that SETD8 suppressed the expression of DUSP10, which was responsible for dephosphorylation of ERK1/2. Mass spectrometry and transcriptional analysis results demonstrated that STAT3 interacted with SETD8 and recruited SETD8 to the promoter region of DUSP10, leading to epigenetic silencing of DUSP10 and the resultant activation of ERK1/2. In conclusion, SETD8 interacts with STAT3 on DUSP10 promoter region and epigenetically silences DUSP10 expression. Decreased DUSP10 expression in PDAC potentiates activation of ERK1/2 phosphorylation, resulting in unfavorable prognosis of PDAC. Highlights: SETD8 is upregulated in PDAC tumors and associated with poor prognosis of patients. RNA expression profiling identifies DUSP10 as a SETD8 downstream target in regulation of ERK1/2 activation. DUSP10 suppresses proliferation of PDAC cell lines and is associated with better prognosis in PDAC patients. SETD8 interacts with STAT3 to suppress DUSP10 expression. SETD8 promotes pancreatic cancer proliferation by monomethylating H4K20 on DUSP10 promoters.